Strategi Pembelajaran pada Pelatihan Bahasa Inggris di Kampung Inggris Sungkai Kota Padang - Novri, M.; Bartin, Tasril (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research was motivated by the learning outcomes of students in English Language training at Kampung Inggris Sungkai City of Padang. This is evidenced by the interest and participation of students in following the learning process, significant improvement in students abilities, the existence of quality resources and achievments, a high level of student success in participating in this training. Researchers suspect the cause of good learning outcomes from students because of the learning strategies implemented in English Language training in Kampung Inggris Sungkai City of Padang. The purpose of this research is to look at learning methods, learning media, learning resources, dan learning techniques on English Language training ini Kampung Inggris Sungkai City of Padang. This type of research is quantitative descriptive research. Population in this study were students in English Language training in Kampung Inggris Sungkai City of Padang, amounting to 20 people . The sampling technique used is Saturated Sample. Samples were taken as much as 100% of the population because the population less than 30 people. Data collection techniques are questionnaires. Questionnaire in the form of a list of questions. Data analysis techniques use the percentage formula. The results showed that the learning strategy in English Language training in Kampung Inggris Sungkai City of Padang are (a) learning strategies on aspect of learning method is very good (b) learning strategies on aspect of learning media is very good. (c) learning strategies on aspect learning resource is very good. (d) learning strategies on aspect learning technique is very good. It is evidenced by the percentage of student answers which reached 83, 90%. Based on the results of this study it is recommended that the institute continue to maintain the learning strategies applied to English Language training in Kampung Inggris Sungkai City of Padang.